Clay Minerals in the Weathering Profile of a Quartz-Muscovite Schist in the Seremban area, Negeri Sembilan - Raj, John Kuna (Universiti Putra Malaysia Press, 1993)
X-ray diffractograms show that randomly interstratified illite-montmorillonite and kaolinite are the clay minerals present in the upper morphological horizons of the weathering profile, while illite is the only clay mineral present in the lowest morphological horizon. In the intermediate morphological horizons, the diffractograms show that kaolinite, illite and randomly interstratified illite-montmorillonite are the clay minerals present. Increasing amounts of randomly interstratified illite-montmorillonite and kaolinite up the weathering profile, and a corresponding decrease of illite, reflect increasing effects of weathering processes; disaggregation and disintegration of muscovites and sericites within the original bedrock material initially resulting in illite, followed by development of the randomly interstratified illite-montmorillonite and kaolinite through leaching of the illites.